The Effectiveness of Problem Based Learning in Improving the Cognitive Abilities of Elementary School Students - Hendri Hendri; Fery Muhamad Firdaus (Juwara: Jurnal Wawasan dan Aksara, 2026)
This study examines the effectiveness of Project Based Learning (PBL) in improving the cognitive abilities of elementary school students, especially critical thinking, problem solving, and conceptual understanding. The research used a quasi-experimental design involving 40 fifth-grade students at Magetan State Elementary School 1. The students were divided into two groups: an experimental group that used PBL and a control group that used conventional learning. Data were collected through cognitive ability tests administered as pre-test and post-test. The results showed that students in the experimental group achieved a higher improvement than those in the control group. The average post-test score in the experimental group increased by 20.1 points, while the control group increased by only 3.5 points. Statistical analysis using t-tests and ANOVA showed a significant difference between the two groups, with p < 0.05. These findings indicate that PBL can improve students’ cognitive abilities and support the development of 21st-century skills. This study suggests that PBL should be integrated into elementary school learning to improve educational quality.